Bases ósseas e musculares dos cortes comerciais do pescoço, tronco e cauda de jacaré-do-pantanal (Caiman yacare Daudin 1802) - Figueiredo, Sandra Izilda Souza de (2013)
Yacare caiman (Caiman yacare) meat consumption has become a marketing trend and a commodity on the rise in Mato Grosso state in Brazil. Commercial exploitation was regulated in 1990, a fact that boosted scientific investigation on the various aspects related to this species. Since characterization of muscle and bone bases of commercial cuts from the yacare caiman has never been reported and is pivotal for the meat industry, it became the main goal of this work. To describe the bones, six boned carcasses from juvenile yacare caimans were used, as well as an adult specimen, obtained by donation after death from the Federal University of Mato Grosso Zoo. Bones were macerated, bleached and anatomical details recorded. To study the muscle, 24 juvenile specimens were obtained after slaughter and skinning, frozen and dissected on both sides immediately after thawing. At the neck region, the only commercial cut is the back sirloin, which has as main base the nine cervical vertebrae, associated to their ribs, and formed by neck muscles, except for the intertransverse cervical and external intercostal cervical muscles. Three cuts are present at the dorsal region. The sirloin cut consists of the semispinal, longissimus and iliocostalis muscles, inserted on thoracic vertebrae and ribs, as well as lumbar and sacral ribs. The meat trims cut is formed by latissimus dorsi, serratus, pectoral and abdominal (external oblique, internal oblique, transversus and rectus) muscles, based in various bones: bone ribs are the thoracic, lumbar, and sacral ribs, the gastralia, the sternum and epipubis. The filet mignon cut is formed by the internal puboishial femoral cranial (sublumbar) muscle and by the troncocaudal (ventral surface of the pelvis) muscle. The commercial meat cuts of the tail are the tail sirloin, composed of semispinal caudal, longissimus caudal, ilioischiocaudal and long caudofemoral muscles, transverse and deep of the tail, as well as the tail tip, consisting of the longissimus caudal and ilioischiocaudal muscles, based on last five or six coccygeal vertebrae. This study on the anatomy of bones and muscles of the commercial cuts from the Caiman yacare is likely to support meat cuts standardization for this species, improving product outcome.